Atividade Antinociceptiva e Antimicrobiana da Casca do Caule de Psidium Cattleyanum Sabine - Alvarenda, F.q.; Royo, V.a.; Mota, B.f.c.; Laurentiz, R.s.; Menezes, E.v.; Melo Junior, A.f.; Oliveira, D.a. (Sociedade Brasileira de Plantas Medicinais, 2015)
ABSTRACT The Psidium cattleyanum Sabine, known as “araçá”, is a native species from the Brazilian Cerrado biome, commonly used, according to ethnobotanical surveis, as a medicinal plant to treat several sicknesses such as liver and , gastric diseases and tissue lesions with painful treatments. The aim of this study was to perform an exploratory screening, investigating the analgesic and antimicrobial activity of the hydroalcoholic extract of the Psidium cattleyanum Sabine (BEPCS) stem bark, in order to support the use of this species as a medicinal plant. For that, the BEPCS and its parts were obtained from the extraction with organic solvents of increasing polarity (hexane, dichloromethane, ethyl acetate and isobutanol), evaluating its phytochemical profile in order to determine the main types of secondary metabolites present in the species. The analgesic activity, through the twisting test in mice, was investigated and induced by acetic acid (0.6%). The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were evaluated using the microdilution technique in liquid against microorganisms of the oral microbiota. The phytochemical screening identified the presence of tannins, saponins, flavonoids and terpenes and/or steroids. The BEPCS exhibited peripheral analgesic activity at the doses of 200 and 400 mg / kg. The AEB (acetate extract bark) and the DEB (dicloromethane extract bark) had better inhibitory effect on bacterial growth of Staphylococcus oraliswith MIC 100 and 150 respectively. The BEPCS demonstrated an inhibitory effect on bacterial growth. The results of experimental studies have indicated the presence of secondary compounds as tannins and flavonoids, which probably can be associated with the analgesic activity and inhibitory effect on the microorganisms tested with BEPCS, fact that justifies the its application.

RESUMO Psidium cattleyanum Sabine, conhecida como “araçá”, é espécie nativa do Bioma Cerrado brasileiro comumente utilizado, segundo levantamento etnobotânico, como planta medicinal para tratar várias doenças tais como: patologias hepáticas, gástricas, lesões teciduais incluindo processos dolorosos. O objetivo deste trabalho foi realizar a triagem fitoquímica com propósito exploratório, investigar a atividade analgésica e antimicrobiana do extrato hidroalcoólico da casca do caule de Psidium cattleyanum Sabine (ECPCS) para apoiar o uso dessa espécie como planta medicinal. Para isso, foram obtidos extratos e frações com solventes orgânicos de polaridade crescente (hexano, diclorometano, acetato de etila e isobutanol) avaliando-se o perfil fitoquímico para determinar as principais classes de metabólitos secundários presentes na espécie. Investigou-se a atividade analgésica pelo teste de contorções abdominais em camundongos induzidas pelo ácido acético (0,6%). A Concentração Inibitória Mínina (CIM) e Concentração Bactericida Mínima (CBM) foram avaliadas através da técnica de microdiluição em caldo contra micro-organismos da microbiota oral. A triagem fitoquímica identificou a presença de taninos, saponinas, flavonoides e terpenos e/ou esteroides. O ECPCS exibiu atividade analgésica periférica nas doses de 200 e 400 mg/kg. O EAC (extrato acetato de casca) o EDC (extrato diclorometânico de casca) desempenharam melhor ação inibitória sobre o crescimento bacteriano de Estafilococos oralis com CIM 100 e 150 respectivamente. O ECPCS desempenhou ação inibitória sobre o crescimento bacteriano. Os resultados dos estudos experimentais comprovaram a presença de compostos secundários tais como, taninos e flavonoides, o que, provavelmente, pode ser associado à atividade analgésica e ao efeito inibitório sobre os micro-organismos testados com o ECPCS, o que justifica o uso medicinal planta.
Antiniciceptive and antimicrobial activity of the stem bark of Psidium cattleyanum Sabine
Keywords: Myrtaceae; araçá; biological activity; inhibition algic; antibacterial activity; Myrtaceae; araçá; atividade biológica; inibição álgica; atividade antibacteriana